The state of world fisheries and aquaculture 2018 : (Food and Agriculture Organization of the United Nations, 2018)
The 2018 edition of this biennial report emphasizes the fisheries and aquaculture sector's role in achieving the 2030 Agenda and measuring progress towards these goals.